An increased NM23H1 copy number may be a poor prognostic factor independent of LOH on 1p in neuroblastomas. - Takeda, O. (Nature Publishing Group, 1996)
In a study of 154 neuroblastomas, loss of heterozygosity (LOH) was observed on 1p (13%, 19/143), 11q (19%, 11/59), 14q (15%, 15/97), 17p (5%, 5/105) and 17q (17%, 9/52). We also found an increase in NM23H1 copy number in 14% (13/95) of neuroblastomas. All except one tumour with an increased copy number stained positive with anti-NM23H1 monoclonal antibody. Event-free survival (EFS) was significantly shorter in 19 patients with LOH on 1p than in 128 without (41% vs 77% 4 year EFS, P=0.0093), and in 13 patients with increased NM23H1 copy numbers than in 82 with normal copy numbers of the gene (61% vs 84% 4 year EFS, P=0.0103). LOH on 11q, 14q or 17q did not affect EFS. Most tumours with LOH on 1p, increased NM23H1 copy numbers or MYCN amplification occurred in patients aged 12 months or more, those with advanced stage disease, and those who showed near diploidy or pseudodiploidy. However, LOH on 1p was found in only 1 of the 13 tumours with increased NM23H1 copy numbers, and MYCN amplification of four copies occurred in only one other such tumour. These findings suggest that the increased NM23H1 copy number may be a predictor for poor prognosis, independent of LOH on 1p, and probably also of MYCN amplification. IMAGES: